The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/eva.12735
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐aggregated planting improves yield in Jerusalem artichoke (Helianthus tuberosus) due to self/non‐self‐discrimination

Abstract: Accumulating evidence indicates that plants are capable of self/non‐self and kin/stranger discrimination. Plants increase biomass of and resource allocation to roots when they encounter roots of conspecific non‐self‐neighbors, but not when they encounter self roots. Root proliferation usually occurs at the expense of reproductive investment. Therefore, if clonal crops are capable of self/non‐self‐discrimination, spatially aggregated planting with seedlings of the same genotype may decrease root proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
11
1
Order By: Relevance
“…We did not find evidence of kin recognition in the invasive Taraxacum species, in contrast to a previous study showing kin recognition in the invasive species Alternanthera philoxeroides (Zhang et al, 2019). This is not surprising considering that studies examining kin recognition have often reported conflicting results (Ehlers & Bilde, 2019;Fukano et al, 2019;Masclaux et al, 2010;Milla, Forero, Escudero, & Iriondo, 2009). It is probable that interaction with kin would differ between plant species with different reproductive and dispersal strategies, so the fitness advantage of kin recognition might be species specific.…”
Section: Lack Of Kin Recognition In T Officinalecontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not find evidence of kin recognition in the invasive Taraxacum species, in contrast to a previous study showing kin recognition in the invasive species Alternanthera philoxeroides (Zhang et al, 2019). This is not surprising considering that studies examining kin recognition have often reported conflicting results (Ehlers & Bilde, 2019;Fukano et al, 2019;Masclaux et al, 2010;Milla, Forero, Escudero, & Iriondo, 2009). It is probable that interaction with kin would differ between plant species with different reproductive and dispersal strategies, so the fitness advantage of kin recognition might be species specific.…”
Section: Lack Of Kin Recognition In T Officinalecontrasting
confidence: 99%
“…The kin recognition hypothesis predicts that plants allocate fewer resources to the roots but more resources to leaf biomass or reproduction in the presence of kin than in the presence of non-related individuals (Fukano et al, 2019). It should be noted, however, that if two genotypes have differential competitive ability, one genotype will increase but the other will decrease root allocation when they grow together compared to when they grow with the same genotype (Ehlers & Bilde, 2019;Masclaux et al, 2010).…”
Section: Lack Of Kin Recognition In T Officinalementioning
confidence: 99%
“…As kin selection can lead to more cooperative traits in plants and greater group performance, its potential use in crop breeding could be considered (Murphy, Swanton, et al, 2017). Kin discrimination has been demonstrated in several crop species, for example, soybean (Murphy, Van Acker, et al, 2017), barley (Ninkovic, 2003), sorghum (Zhang et al, 2016), wheat (Zhu & Zhang, 2013, but see Fréville et al, 2019), rice (Yang et al, 2018) and Jerusalem artichoke ( Helianthus tuberosus , Fukano, Guo, Noshita, Hashida, & Kamikawa, 2019), with findings that kin‐interacting plants tend to exhibit more cooperative root systems. A question then arises: to what would extent crop selection for kin recognition and discrimination be an effective means to increase crop yields?…”
Section: Kin Selection and Cropsmentioning
confidence: 99%
“…Because this experiment had different research purposes, some plants were paired or grouped, but these plants did not affect the growth of focal individuals grown singly and were omitted from the subsequent analyses. For more details, see our previous study (Fukano et al, 2019).…”
Section: Growth and Measurement Of Helianthus Tuberosusmentioning
confidence: 99%